2018
DOI: 10.1159/000487786
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Antitumor Effect of BKM120 with Prima-1Met Via Inhibiting PI3K/AKT/mTOR and CPSF4/hTERT Signaling and Reactivating Mutant P53

Abstract: Background/Aims: PI3KCA and mutant p53 are associated with tumorigenesis and the development of cancers. NVP-BKM120, a selective pan-PI3K inhibitor, exerts the antitumor activity by suppressing the PI3K signaling pathway. Prima-1Met, a low molecular weight compound, can rescue the gain-of-function of mutant p53 by restoring its transcriptional function. In this study, we investigated whether PI3K inhibition combined with mutant p53 reactivation could enhance the antitumor effect in thyroid cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In this context, the molecule PRIMA-1Met reactivates mutant p53 and has been already tested in melanoma, showing encouraging results in combination with the BRAF and MEK inhibitors [73,74]. Recently, the pan PI3K inhibitor NVP-BKM120, causing the suppression of PI3K downstream signaling, has been associated with the PRIMA-1Met and displayed synergistic antitumour effects both in vitro and in vivo thyroid cancer, thus opening the doors to a potential novel approach to the thyroid cancer treatment [75].…”
Section: Combination To Pi3k Inhibitormentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, the molecule PRIMA-1Met reactivates mutant p53 and has been already tested in melanoma, showing encouraging results in combination with the BRAF and MEK inhibitors [73,74]. Recently, the pan PI3K inhibitor NVP-BKM120, causing the suppression of PI3K downstream signaling, has been associated with the PRIMA-1Met and displayed synergistic antitumour effects both in vitro and in vivo thyroid cancer, thus opening the doors to a potential novel approach to the thyroid cancer treatment [75].…”
Section: Combination To Pi3k Inhibitormentioning
confidence: 99%
“…The current targets known for this molecule are VEGFR1-3, fibroblast growth factor receptors 1-4 (FGFR1-4), RET, c-kit, PDGFRa, and mast/stem cell growth factor receptor (SCFR) [81]. These molecules thus interact with many essential functions of cancer cells as proliferation, apoptosis, autophagy, and angiogenesis [75], but, alone, weak antiproliferative properties are observed for sorafenib and for lenvatinib, clinical studies discussed below showed adverse effects for >50% of patients included hypertension, diarrhea, or decreased appetite [81]. In this context, the strategy to combine these molecules to potentiate their properties with other molecules has been the object of preclinical studies described below.…”
Section: Vegf Inhibitor Used As a Single Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been proven that NVP-BKM120 suppresses downstream factors of PI3K, including downregulation of p-Akt and p-S6R and cancer stem markers. A previous study by our group suggested that synergistic action of BKM120 and Prima-1 Met effectively suppressed the proliferation and migration and promoted the differentiation of thyroid cancer cells in vivo and in vitro (19). Radiation therapy is another important treatment for thyroid cancer, but low-dose radiation induces the activation of the PI3K/Akt/mTOR pathway, leading to the occurrence of epithelial-mesenchymal transition (EMT).…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%